2019
DOI: 10.5194/essd-11-221-2019
|View full text |Cite
|
Sign up to set email alerts
|

A long-term (2002 to 2017) record of closed-path and open-path eddy covariance CO<sub>2</sub> net ecosystem exchange fluxes from the Siberian Arctic

Abstract: Abstract. Ground-based observations of land–atmosphere fluxes are necessary to progressively improve global climate models. Observed data can be used for model evaluation and to develop or tune process models. In arctic permafrost regions, climate–carbon feedbacks are amplified. Therefore, increased efforts to better represent these regions in global climate models have been made in recent years. We present a multi-annual time series of land–atmosphere carbon dioxide fluxes measured in situ with the eddy covar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 83 publications
3
24
0
Order By: Relevance
“…Previous research based at the research site has focused on greenhouse gas cycling (Abnizova et al, 2012;Knoblauch et al, 2018Knoblauch et al, , 2015Kutzbach et al, , 2007Langer et al, 2015;Runkle et al, 2013;Sachs et al, 2010Sachs et al, , 2008Holl et al, 2019), aquatic biology (Abramova et al, 2017), upscaling of land surface characteristics and parameters from ground-based data to remote-sensing data (Cresto Aleina et al, 2013;Muster et al, , 2012, and hydrology (Boike et al, 2008b;Fedorova et al, 2015;Helbig et al, 2013). Data from a few years have also been used in earth system modelling (Chadburn et al, 2015(Chadburn et al, , 2017Ekici et al, 2014Ekici et al, , 2015 and for modelling land surface, snow, and permafrost processes Langer et al, 2016;Westermann et al, 2016Westermann et al, , 2017Yi et al, 2014;Aas et al, 2019).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Previous research based at the research site has focused on greenhouse gas cycling (Abnizova et al, 2012;Knoblauch et al, 2018Knoblauch et al, , 2015Kutzbach et al, , 2007Langer et al, 2015;Runkle et al, 2013;Sachs et al, 2010Sachs et al, , 2008Holl et al, 2019), aquatic biology (Abramova et al, 2017), upscaling of land surface characteristics and parameters from ground-based data to remote-sensing data (Cresto Aleina et al, 2013;Muster et al, , 2012, and hydrology (Boike et al, 2008b;Fedorova et al, 2015;Helbig et al, 2013). Data from a few years have also been used in earth system modelling (Chadburn et al, 2015(Chadburn et al, , 2017Ekici et al, 2014Ekici et al, , 2015 and for modelling land surface, snow, and permafrost processes Langer et al, 2016;Westermann et al, 2016Westermann et al, , 2017Yi et al, 2014;Aas et al, 2019).…”
Section: Site Descriptionmentioning
confidence: 99%
“…These individual process-based fluxes governing the CO 2 balance respond differently to changing climatic conditions such as temperature and moisture. For instance, it was shown that temperature changes in arctic soils could cause a significant increase in the CO 2 uptake via GPP (Shaver et al, 1998;Oberbauer et al, 2007;Natali et al, 2012;Mauritz et al, 2017), which can be, beside other factors, attributed to shifts in vegetation composition (Elmendorf et al, 2012;Hudson et al, 2011) and increased nutrient availability (Johnson et al, 2000;Salmon et al, 2016;Beermann et al, 2015). Furthermore, the effect of drainage on GPP remains uncertain; some studies found drainage of arctic soils to reduce GPP (Merbold et al, 2009;Chivers et al, 2009;Kwon et al, 2016), while other studies found drainage to lead to a slight increase in GPP (Olivas et al, 2010;Kittler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive description of the EC approach is given, for example, by Aubinet et al (2012). Half-hourly turbulent CO 2 fluxes were computed using the software EddyPro 6.2.0 (LI-COR, USA) and included the following standardized steps; see Holl (2017); Holl et al (2019).…”
Section: Flux Calculation and Quality Filteringmentioning
confidence: 99%
“…Correction factors F 1 were calculated with two methods depending on sensible and latent heat fluxes being above (high fluxes) or below (low fluxes) the thresholds of 10 and 5 W m −2 respectively (Fratini et al, 2012). For high fluxes, EddyPro calculated the correction factors as proposed by Hollinger et al (1999). F 1 estimation included the degradation of the unattenuated sensible heat flux cospectrum by multiplying it with H IIR (f n /f c ) for the previously determined f c .…”
Section: Flux Calculation and Quality Filteringmentioning
confidence: 99%